Subversion and Utilization of Host Innate Defense by Leishmania amazonensis - Soong, Lynn (Frontiers in Immunology, 2012)
Infection with Leishmania amazonensis and other members of the L. mexicana complex can lead to diverse clinical manifestations, some of which are relatively difficult to control, even with standard chemotherapy. Diffuse cutaneous leishmaniasis is a rare but severe form, and its clinical hallmark is excessive parasitic growth in infected cells accompanied by profound impairments in host immune responses to the parasites. Since these parasites also cause non-healing cutaneous leishmaniasis in most inbred strains of mice, these animals are valuable models for dissecting the mechanisms of persistent infection and disease pathogenesis. In comparison to other Leishmania species, L. amazonensis infections are most remarkable for their ability to repress the activation and effector functions of macrophages, dendritic cells and CD4+ T cells, implying discrete mechanisms at work. In addition to this multilateral suppression of host innate and adaptive immunity, the activation of types I and II interferon-mediated responses and autophagic/lipid metabolic pathways actually promotes rather than restrains L. amazonensis infection. These seemingly contradictory findings reflect the remarkable adaptation of the parasites to the ancient defense machinery of the host, as well as the complex parasite-host interactions at different stages of infection, which collectively contribute to non-healing leishmaniasis in the New World. This review article highlights new evidence that reveals the strategies utilized by L. amazonensis parasites to subvert or modulate host innate defense machinery in neutrophils and macrophages, as well as the regulatory roles of host innate responses in promoting parasite survival and replication within the huge parasitophorous vacuoles. A better understanding of unique features in host responses to these parasites at early and late stages of infection is important for the rational design of control strategies for non-healing leishmaniasis.